Effect of drop height on vertical jumping performance in pre-, circa-, and post-pubertal boys and girls - Birat, A.; Sebillaud, D.; Bourdier, P.; Doré, E.; Duché, P.; Blazevich, A. J.; Patikas, D.; Ratel, S. (Pediatric Exercise Science, 2020)
Purpose: To examine the effect of drop height on vertical jumping performance in children with respect to sex and maturity status. Methods: Thirty-seven pre-pubertal, 71 circa-pubertal, and 69 post-pubertal boys and girls performed, in a randomized order, 2 squat jumps, 2 countermovement jumps, and 2 drop jumps (DJ) from heights of 20, 30, 40, 50, 60, and 70 cm. The trial with the best jump height in each test was used for analysis. Results: No significant sex × maturity status × jump type interaction for jump height was observed. However, on average, the children jumped higher in the countermovement jump than in squat jump and DJs (+1.2 and +1.6 cm, P < .001, respectively), with no significant differences between DJs and squat jumps or between DJs when increasing drop heights. Regarding DJs, 59.3% of the participants jumped higher from drop heights of 20 to 40 cm. Conclusions: Children, independent of sex and maturity status, performed best in the countermovement jump, and no performance gain was obtained by dropping from heights of 20 to 70 cm. During maturation, the use of drop heights between 20 and 40 cm may be considered in plyometric training, but the optimum height must be obtained individually.